More uneven distributions overturn benefits of higher precipitation for crop yields. (2nd February 2016) - Fishman, Ram
Abstract: Climate change is expected to lead to more uneven temporal distributions of precipitation, but the impacts on human systems are little studied. Most existing, statistically based agricultural climate change impact projections only account for changes in total precipitation, ignoring its intra-seasonal distribution, and conclude that in places that will become wetter, agriculture will benefit. Here, an analysis of daily rainfall and crop yield data from across India (1970–2003), where a fifth of global cereal supply is produced, shows that decreases in the number of rainy days have robust negative impacts that are large enough to overturn the benefits of increased total precipitation for the yields of most major crops. As an illustration, the net, mid 21st century projection for rice production shifts from +2% to −11% when changes in distribution are also accounted for, independently of additional negative impacts of rising temperatures.